Village Fund Pathology and Supervisory Dysfunction: A Legal Analysis in Boalemo Regency - Pade, Sri Rahayu Lestari; Rasdianah, Rasdianah (CV. Social Politic Genius (SIGn), 2025)
Indonesia’s Village Fund policy faces a serious challenge in the form of systematic financial misuse, which is exacerbated by a weak internal oversight mechanism. This research aims to analyze the modus operandi of Village Fund misuse and the institutional dysfunction of the Inspectorate in performing its supervisory functions in Boaloemo Regency. Using an empirical juridical approach and a qualitative study design, primary data were collected through in-depth interviews, observation, and questionnaires, supported by secondary data from a document analysis. The results indicate a governance pathology at the village level, manifested through authoritative deviation, financial manipulation, and administrative engineering. This condition is triggered by a lack of participation and transparency. Furthermore, the study finds that this pathology is directly caused by the dysfunction of the Inspectorate, which suffers from structural constraints including resource deficits (budget and auditors), geographical challenges, an excessive workload, and a lack of sanctioning authority that blunts the deterrence effect. It is concluded that a strong causal relationship exists, wherein the failure of the internal oversight function is the determining factor that creates a permissive environment for widespread misappropriation. Therefore, three strategic policies are recommended: the institutional capacity building of the Inspectorate, the revitalization of participatory oversight mechanisms at the village level, and the enhancement of competency standards for village apparatus human resources.